Zarys dziejów powojennej administracji Ziemi Lubuskiej na przykładzie powiatu słubickiego = The historical outline of post-war administration of Lubusz Land on the example of the poviat of Słubice - Utracki, Damian (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article which I have suggested depicts post-war transformations of administrative system on Lubusz Land. It contains information from 1945 (directly from the germ of creating administration in the final stage of the Second World War on the so called Regained Territories) to the recent administrative reform of the whole country from 1999, on the strength of which 16 new voivodeships were established, including Lubusz Voivodeship. The entirety of the subject matter has been expressed pursuant to, or rather on the example of post-war history of the poviat of Słubice where one may definitely notice the complexity of issues of Regained Territories (administrative afliliation, management, and the like).
Keywords: Ziemia Lubuska; województwo lubuskie; administracja lokalna; Słubice; historia; po 1944 r.